PENGARUH EDUKASI KESEHATAN TERHADAP PENINGKATAN EFIKASI DIRI PADA PENYANDANG DIABETES MELITUS TIPE 2 : LITERATURE REVIEW - Tri Rahayu; Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2025)
ABSTRACT Background: Type 2 Diabetes Mellitus (T2DM) accounts for around 90% of all diabetes cases and is at risk of experiencing acute complications such as hypoglycemia, DKA, and HHNS. The three main factors that influence self-management of T2DM patients are knowledge, disease duration, and self-efficacy. High self-efficacy plays an important role in patient compliance with self-management. Improving self-efficacy can be done through health education, one of which is through the Diabetes Self Management Education (DSME) program. The purpose of this study was to determine the effect of education on self-efficacy in T2DM patients. Method: using the literature review method, the search method using Google Scholar, after searching and looking at the year of publication, title suitability and quality assessment, six selected articles were obtained, Research Results: shows that educational interventions are effective in increasing self-efficacy. Conclusion: education provided through various educational methods such as videos, e-modules, group discussions, and digital media has been shown to increase patient confidence in managing the disease independently. Keywords: Education, Self-Efficacy, Type 2 Diabetes Mellitus